2013
DOI: 10.17925/usor.2013.06.01.15
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Diagnosis and Monitoring Using Advanced Imaging Technologies

Abstract: Advanced ocular imaging technologies facilitate objective and reproducible quantification of change in glaucoma but at the same time, impose new challenges on scientists and clinicians for separating true structural change from imaging noise. This review examines time-domain and spectral-domain optical coherence tomography, confocal scanning laser ophthalmoscopy and scanning laser polarimetry technologies and discusses the diagnostic accuracy and the ability of each technique for evaluation of glaucomatous pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 126 publications
1
6
0
Order By: Relevance
“…In addition to cup/disc ratios, the evaluation of the RNFL thickness by OCT and HRT-III can be useful in the clinical setting, as certain RNFL characteristics were associated with a shorter time to functional disease progression over the course of five years. Similar to our findings, Sehi et al showed that progressive RNFL loss was associated with functional glaucoma progression [13], while Lalezary et al showed that thinner baseline RNFL, as measured by OCT, was an independent predictor of functional glaucomatous changes [14]. Our data also show that baseline optic disc cup shape, based on measures of the topography including cup size, cup depth, neuroretinal rim slope, and RNFL curvature, appears to be a significant predictor of glaucoma progression.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…In addition to cup/disc ratios, the evaluation of the RNFL thickness by OCT and HRT-III can be useful in the clinical setting, as certain RNFL characteristics were associated with a shorter time to functional disease progression over the course of five years. Similar to our findings, Sehi et al showed that progressive RNFL loss was associated with functional glaucoma progression [13], while Lalezary et al showed that thinner baseline RNFL, as measured by OCT, was an independent predictor of functional glaucomatous changes [14]. Our data also show that baseline optic disc cup shape, based on measures of the topography including cup size, cup depth, neuroretinal rim slope, and RNFL curvature, appears to be a significant predictor of glaucoma progression.…”
Section: Plos Onesupporting
confidence: 90%
“…Similar to our findings, Sehi et al . showed that progressive RNFL loss was associated with functional glaucoma progression [ 13 ], while Lalezary et al . showed that thinner baseline RNFL, as measured by OCT, was an independent predictor of functional glaucomatous changes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroretinal rim area is measured in 6 sectors (temporal superior, nasal superior, nasal, nasal inferior, temporal inferior and temporal) as well as globally. RNFL thickness is measured as the difference between the inner margin of the ILM (internal limiting membrane) and the outer margin of the RNFL and the obtained values are automatically compared to a normative database [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 7 The RNFL can be assessed using either scanning laser polarimetry, currently available as the GDx-PRO (Glaucoma Diagnostics [GDx] Carl Zeiss Meditec, Dublin, CA) 8 or spectral-domain optical coherence tomography (OCT), with several commercial devices available. 9 These imaging tests are user friendly and provide automated quantitative classifications. 10 …”
mentioning
confidence: 99%